2012
DOI: 10.1007/s10858-012-9621-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of errors in 15N transverse relaxation rates measured using various CPMG phasing schemes

Abstract: Nitrogen-15 Carr-Purcell-Meiboom-Gill (CPMG) transverse relaxation experiment are widely used to characterize protein backbone dynamics and chemical exchange parameters. Although an accurate value of the transverse relaxation rate, R2, is needed for accurate characterization of dynamics, the uncertainty in the R2 value depends on the experimental settings and the details of the data analysis itself. Here, we present an analysis of the impact of CPMG pulse phase alternation on the accuracy of the 15N CPMG R2. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Each set of best-fit parameters obtained from global fits of eq was validated in Mathematica 8.0 by generating 500 synthetic data sets, each randomly noise-corrupted by a Gaussian distribution whose standard deviation (SD) is given by the average experimental uncertainty of all R 2 (1/ τ cp ) points included in that data set. These synthetic data sets were each refit with eq , and the resulting statistics of best-fit parameters were used to gauge the validity of the original fit. These results are summarized in SI Figure 1 and validate the robustness of this fitting scheme. Residues whose conformational exchange motion was in the fast limit at pH 5.5 were analyzed with eq , where usable dispersion data were available (10–20 °C) In summary, the following residues were included in global analyses of CPMG data: pH 7.0 : cluster 1: S16, T17, F46, V47, T82, D83, and Q101; cluster 2: A64, K66, T70, and N71.…”
Section: Methodsmentioning
confidence: 83%
“…Each set of best-fit parameters obtained from global fits of eq was validated in Mathematica 8.0 by generating 500 synthetic data sets, each randomly noise-corrupted by a Gaussian distribution whose standard deviation (SD) is given by the average experimental uncertainty of all R 2 (1/ τ cp ) points included in that data set. These synthetic data sets were each refit with eq , and the resulting statistics of best-fit parameters were used to gauge the validity of the original fit. These results are summarized in SI Figure 1 and validate the robustness of this fitting scheme. Residues whose conformational exchange motion was in the fast limit at pH 5.5 were analyzed with eq , where usable dispersion data were available (10–20 °C) In summary, the following residues were included in global analyses of CPMG data: pH 7.0 : cluster 1: S16, T17, F46, V47, T82, D83, and Q101; cluster 2: A64, K66, T70, and N71.…”
Section: Methodsmentioning
confidence: 83%
“…From an experimental approach, NMR investigations of protein conformational exchange and dynamics have a strong hold. , Although the backbone dynamics of the native subtype B construct have been explored extensively, ,,,, the exchange rates in native HIV-1 PR are difficult to characterize due to the fast dynamics of the flaps and relatively slower time scale of the exchange process . Recently, exchange dynamics were measured on a synthetic tethered HIV-1 PR construct revealing that mutations may alter the rate of exchange among the states, thus impacting catalysis .…”
Section: Discussionmentioning
confidence: 99%
“…The differential relaxation rates may cause the R 2 eff values to depend on the number of π pulses applied during a constant period, i.e., ν cpmg . A few groups have demonstrated that the application of four consecutive CPMG refocusing π pulses with phases {y, y, x, −x} for CPMG 1 and {x, x, y, −y} for CPMG 2 , respectively, suppresses many artifacts by mixing the transverse (R 2 ) and longitudinal (R 1 ) relaxation rates of 15 N magnetization during the pulse application periods [25][26][27][28]. The method, however, did not improve the result for ChiA1.…”
Section: Artifacts Observed In Amide 15 N Spin Rd Experimentsmentioning
confidence: 99%